PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN FLASH CARD TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS - Yustrian Bawono Saputro; Lukki Lukitawati (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Social Studies learning in schools is often still dominated by conventional teaching methods, which may lead to low student learning interest. This study aimed to examine the effect of the Teams Games Tournament (TGT) learning model assisted by Flash Card media on students’ learning outcomes and learning interest in Social Studies. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants were eighth-grade students of SMP Negeri 12 Semarang, where class VIII G was assigned as the experimental group and class VIII F as the control group. Data were collected using learning outcome tests (pretest–posttest) and a learning interest questionnaire, and were analyzed using the Independent Sample t-test. The results indicated that the experimental group achieved higher learning outcomes and learning interest compared to the control group. The t-test results showed a significance value of 0.032 for learning outcomes and 0.002 for learning interest (p < 0.05), indicating that the implementation of the TGT learning model assisted by Flash Card media had a significant effect. Therefore, the TGT learning model assisted by Flash Card media is effective in improving students’ learning outcomes and learning interest in Social Studies. ABSTRAK Pembelajaran IPS di sekolah seringkali masih didominasi metode konvensional yang berdampak pada rendahnya minat belajar siswa. Penelitian ini bertujuan untuk menguji pengaruh penerapan model pembelajaran Teams Games Tournament (TGT) berbantuan media Flash Card terhadap hasil belajar dan minat belajar siswa pada mata pelajaran IPS. Penelitian menggunakan pendekatan kuantitatif dengan jenis quasi experiment dan desain Nonequivalent Control Group Design. Subjek penelitian adalah siswa kelas VIII SMP Negeri 12 Semarang, dengan kelas VIII G sebagai kelas eksperimen dan kelas VIII F sebagai kelas kontrol. Teknik pengumpulan data menggunakan tes hasil belajar (pretest–posttest) dan angket minat belajar, sedangkan analisis data dilakukan menggunakan uji Independent Sample t-test. Hasil penelitian menunjukkan bahwa rata-rata hasil belajar dan minat belajar siswa pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol, serta diperoleh nilai signifikansi uji t sebesar 0,032 pada hasil belajar dan 0,002 pada minat belajar (p < 0,05), yang menunjukkan adanya pengaruh signifikan penerapan model pembelajaran TGT berbantuan media Flash Card. Dengan demikian, model pembelajaran TGT berbantuan media Flash Card terbukti efektif dalam meningkatkan hasil belajar dan minat belajar siswa pada mata pelajaran IPS.